2019
DOI: 10.3389/fphys.2019.01315
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde Induces an Endothelium-Dependent Relaxation of Superior Mesenteric Artery: Potential Role in Postprandial Hyperemia

Abstract: Acetaldehyde (AA) is a small, ubiquitous compound present in foods, beverages, as a gas phase combustion product, and also endogenously generated from metabolism as from ethanol (EtOH). Acetate is a short chain fatty acid derived from AA oxidation, and acetate levels were significantly higher in urine collected overnight with food provided ad libitum compared with urine collected after 9 h fasting. Feeding increases gastrointestinal blood flow, and thus, we explored the direct effects of AA (and acetate) in is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Its best known effect is vascular relaxation, a response typically found in pulmonary (Greenberg et al, 1993), mesenteric (Ru et al, 2008), cutaneous Altura, 1982, 1987) and cerebral blood vessels (Altura and Altura, 1999), which has been attributed to the potentiation of NO-dependent and NO-independent vasodilation pathways (Rocha et al, 2012;Tawakol et al, 2019). In certain vascular beds ethanol-induced vasodilation is rather attributed to its metabolite acetaldehyde, which mediates an endothelium-dependent relaxation (Jin et al, 2019) in mesenteric vessels. Furthermore, acetate, a metabolite of aldehyde also displays a moderate vasodilator response (Altura and Altura, 1982).…”
Section: Interaction Of Ethanol On Menthol Receptorsmentioning
confidence: 99%
“…Its best known effect is vascular relaxation, a response typically found in pulmonary (Greenberg et al, 1993), mesenteric (Ru et al, 2008), cutaneous Altura, 1982, 1987) and cerebral blood vessels (Altura and Altura, 1999), which has been attributed to the potentiation of NO-dependent and NO-independent vasodilation pathways (Rocha et al, 2012;Tawakol et al, 2019). In certain vascular beds ethanol-induced vasodilation is rather attributed to its metabolite acetaldehyde, which mediates an endothelium-dependent relaxation (Jin et al, 2019) in mesenteric vessels. Furthermore, acetate, a metabolite of aldehyde also displays a moderate vasodilator response (Altura and Altura, 1982).…”
Section: Interaction Of Ethanol On Menthol Receptorsmentioning
confidence: 99%
“…Brd2, Brd3 and Brd4 are three major members mediating a variety of biological responses of the BET family proteins ( Morgado-Pascual et al, 2019 ). As first step toward understanding the effect of I-BET151, a highly selective BET inhibitor, on the pathogenesis of HN, we examined the expression of Brd2, Brd3 and Brd4 in the kidneys of rats with or without HN.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the transcription of genes involved in inflammation and other pathological processes in renal diseases are regulated by epigenetic changes ( Nangaku et al, 2017 ; Morgado-Pascual and Marchant, 2018 ). Epigenetic modifications, in particular histone acetylation, are dynamic processes in normal and diseased states ( Reddy and Natarajan, 2015 ; Morgado-Pascual et al, 2019 ). It is well documented that histone acetylation is positively regulated by histone transferases and negatively regulated by histone deacetylases ( Guo et al, 2019 ; Tang and Zhuang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations